Fundamentals of inheritance (Faraid) in Islam: ensuring fair distribution - Karim, Fatimah (Islam on Web: The Window to Islam, 2024)
Faraid, the Islamic law of inheritance, is a fundamental component of Shariah that ensures the just and equitable distribution of a deceased person's estate among rightful heirs [1]. Rooted in the Qur'an, Hadith and Islamic jurisprudence, Faraid addresses both the spiritual and social dimensions of wealth distribution, aiming to prevent disputes and maintain family harmony. This article explores the definition, pillars, conditions, allocation of Faraid, obstacles to receiving inheritance, and practical examples of inheritance calculation.